Grafomotricidad y pre-escritura en niños de 4 a 5 años, Escuela de Educación Básica Municipal Héroes del Cenepa, ciudad de Loja, período 2023-2024. - Jiménez Macas, Nayely Jessenia (2024)
Pre-writing refers to a series of activities that the child must perform to begin the writing process. When reaching this stage, it is crucial to carry out exercises gradually and appropriate to their age, allowing them to develop the ability to grab crayons or other materials to make scribbles. The research was conducted in order to determine whether graphomotor skills influence the learning of pre-writing in children aged 4 to 5 years at the Heroes del Cenepa Municipal Basic Education School, in the city of Loja. Likewise, the mixed approach was implemented to analyze and collect information in a quantitative and qualitative manner. The descriptive scope also facilitated the description of the variables under study; the quasi-experimental design allowed the manipulation of graphomotor skills to demonstrate the effectiveness in pre-writing; the analytical-synthetic and inductive-deductive methods contributed to the construction of the theoretical framework and the analysis of the information to reach general conclusions; the instrument used, Lorenzo Filho's ABC Test, designed for children from 4 to 6 years old, proved the difficulties they presented at the beginning of prewriting, where 80% of the children were at a low and lower level at the beginning of the research; After applying the activity guide based on graphomotor activities, the efficacy of the intervention was verified by observing that 60% of the children were able to reach the medium and higher levels. It is concluded that the use of graphomotor skills as a methodological strategy favors the area of pre-writing, where improvements were noted regarding the development of muscle tone, fine motor skills, motor strength and the acquisition of significant learning, increasing the essential skills for the writing process. Key words: coordination, graphism, fine motor skills, eye-hand, graphic representation.